2017
DOI: 10.1128/iai.00343-17
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of the Chicken Tracheal Response to Virulent Mycoplasma gallisepticum Strain R low

Abstract: , the primary etiologic agent of chronic respiratory disease (CRD) in poultry, leads to prolonged recruitment and activation of inflammatory cells in the respiratory mucosa. This is consistent with the current model of immune dysregulation that ostensibly allows the organism to evade clearance mechanisms and establish chronic infection. To date, studies using quantitative reverse transcription-PCR (qRT-PCR) and microarrays have shown a significant transient upregulation of cytokines and chemokines from trachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 33 publications
(50 reference statements)
3
64
1
Order By: Relevance
“…Previous transcriptomic analysis conducted in our laboratory indicated a massive and dynamic host tracheal response associated with virulent R low infection over 7 days, highlighting the immunological, metabolic, and stress-and injury-related genes and pathways which may contribute to the exaggerated and dysregulated host response (10). To better understand differences between virulent and nonimmunopathologic host responses, we conducted a 2-day infection study followed by RNA sequencing (RNA-Seq) to assess the host transcriptional differences in genes and pathways leading to either a maladaptive or beneficial immune response to M. gallisepticum (25). Responses against intratracheally administered GT5 and Mg7 LAVs were compared to responses against R low at early time points postinfection.…”
mentioning
confidence: 83%
“…Previous transcriptomic analysis conducted in our laboratory indicated a massive and dynamic host tracheal response associated with virulent R low infection over 7 days, highlighting the immunological, metabolic, and stress-and injury-related genes and pathways which may contribute to the exaggerated and dysregulated host response (10). To better understand differences between virulent and nonimmunopathologic host responses, we conducted a 2-day infection study followed by RNA sequencing (RNA-Seq) to assess the host transcriptional differences in genes and pathways leading to either a maladaptive or beneficial immune response to M. gallisepticum (25). Responses against intratracheally administered GT5 and Mg7 LAVs were compared to responses against R low at early time points postinfection.…”
mentioning
confidence: 83%
“…The vaccine strains Mg7 and GT5 show a significant reduction in virulence (6,16) in the host and do not show the same initial progression of vlhA gene expression as that shown by wild-type virulent R low . Additionally, M. gallisepticum GT5 and Mg7 do not cause the same host cell stress response or immune dysregulation (J. Beaudet, unpublished data) that is observed in chickens experimentally challenged with virulent wild-type R low (18). It is possible that since the trachea is not being disrupted or damaged by the vaccine strains, the vlhA genes are not forced to change in response.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies demonstrated that MG is the primary cause of chronic respiratory disease in chickens and infectious sinusitis in turkeys, characterized by nasal discharge, sneezing, and coughing (2,3). Researchers reported that MG-infection causes significant economic losses to the poultry industry including the reduction in egg production, hatchability, and low meat quality (4)(5)(6). MGinfection induces respiratory distress, profound inflammatory response in mucosal tissues and immune dysregulation in chickens (4).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported that MG-infection causes significant economic losses to the poultry industry including the reduction in egg production, hatchability, and low meat quality (4)(5)(6). MGinfection induces respiratory distress, profound inflammatory response in mucosal tissues and immune dysregulation in chickens (4). Moreover, the property of cytoadherence of MG produced additional virulence factors including superoxide radicals leading to immune dysregulation (4,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation